Application of Regional Regulation Number 23 of 2013 in Improving the Quality of Sorong City Government Apparatus - Kalagison, Miryam Diana; Imran, Imran; Ismail, Ismail; Nonce, Nurmi (PINISI Discretion Review, 2021)
This study aims to analyze the application of Regional Regulation no. 38 of 2013 on the Effectiveness of Sorong City Government Apparatus Resources carried out by Sorong City government officials by providing development of Sorong City government apparatus resources through education and training, and to analyze Determinant factors in Improving the Quality of Sorong City Government Apparatus Resources regarding the computer skills possessed by the Sorong City government apparatus, the facilities and infrastructure in the Sorong City government apparatus, the working time of the Sorong City government apparatus, the level of education possessed by the Sorong City government apparatus, the performance of the apparatus, the competence of the apparatus and the discipline of the Sorong City government apparatus. This research is descriptive qualitative data obtained from several informants. The results showed that the application of Regional Regulation No. 38 of 2013 on the effectiveness of Sorong City government apparatus resources. Regarding development and education in Sorong City on the effectiveness of apparatus resources, it has been going well but is still far from what is expected because education has not been implemented thoroughly for the apparatus and community in Sorong City.